Kharakteristik Masa Pembinaan Pendidikan Islam pada Masa Rasulullah (Makkah dan Madinah) - Aini Nur Ma'rifah (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2022)
The implementation of education at the time of the Prophet can be divided into two stages, namely the stage of education carried out in Mecca, and the stage of education carried out in Medina. During the development of Islamic education in the Mecca period, there were three stages of education, namely the hidden stage, the overt stage and the general appeal. Islamic education materials are monotheism and the Koran. Islamic education, namely lectures, dialogues, discussions or questions and answers, parables, stories, habituation and memorization. The educational institution is in the house of Arqam and Kuttab. During the development of Islamic education in the Medina period, the Prophet carried out activities, namely establishing mosques and forming the state of Medina. The material for Islamic education is to deepen and expand the material that has been taught in Mecca, order, social, economic, political and the welfare of the people. Islamic educational institutions are mosques and suffahs.